Prefabrication of two-dimensional Ni–W/TiN films on oil-gas X52 steels by pulse electrodeposition - Zhang, Yu (2022)
The main aim of this investigation was to prefabricate two-dimensional Ni–W/TiN films on oil-gas X52 steel substrates via pulse electrodeposition (PE). The influences of the TiN content in the bath on the surface morphology, nano-hardness, wear, and corrosion properties of the films were also discussed. The results indicated that the TiN particle size was only ∼33 nm in 8 g/L TiN electrolyte, which was ∼2.4 times less than that of TiN in 16 g/L solution. The Ni–W/8TiN film exhibited a uniform, smooth surface, and the depression depth and protrusion height were 45.3 nm and 81.7 nm, respectively. Three diffraction peaks at 43.72, 50.78, and 75.26° in the Ni–W/4TiN film emerged as the sharpest and narrowest peaks among the four films. Three XPS peaks for the Ni 2p3/2 were present at 852.13, 856.35, and 861.87 eV in the Ni–W/8TiN film, corresponding to Ni, Ni2+ (Ni(OH)2), Ni3+ (NiOOH) species. Besides, the XPS peak of W 4f7/2, which located at 33.85 eV belonged to elemental W. The Ni–W/8TiN film had the lowest wear depth and width at 32.1 μm and 5.7 mm, respectively. Only some narrow and shallow scratches were found on the Ni–W/8TiN film surface, showing its outstanding tribological properties among the films tested. In addition, the Ni–W/4TiN film showed the highest mean frictional coefficient of 0.73, which was ∼1.6 times more than that of the Ni–W/8TiN film.